Kewenangan Mahkamah Konstitusi sebagai Positive legislator (Studi Putusan Mahkamah Konstitusi Nomor 135/PUU-XXII/2024) - Deny Setiyo Utomo; Sulaksono Sulaksono; Hananto Widodo (Fakultas Hukum Universitas Islam Jember, 2026)
Constitutional Court Decision Number 135/PUU-XXII/2024 raises legal issues related to the limits of the Constitutional Court's authority in determining the model for conducting elections. This study aims to analyze the Constitutional Court's authority as a positive legislator in Decision Number 135/PUU-XXII/2024, as well as to explain the legal consequences resulting from that decision. The research method used is normative research with statutory, conceptual, and case approaches. The results of the study show that through this decision, the Constitutional Court has exceeded its capacity in reviewing laws against the 1945 Constitution by creating new norms through constitutional interpretation that determines the separation of the implementation of national and regional elections, along with their schedules. The separation of elections by the Constitutional Court is not based on a legal vacuum or urgent circumstances, but rather on technical and managerial considerations in election administration, which should fall within the legislature's domain as part of open legal policy. The legal consequences of Constitutional Court Decision Number 135/PUU-XXII/2024 raise several constitutional issues, including the potential violation of the principle of five-year election periodicity, the merging of the general election and regional election regimes which are constitutionally regulated differently, the narrowing of the constitutional interpretation of Article 18 paragraph (4) of the 1945 Constitution, and the potential vacancies of regional heads and members of regional representative councils during the transition period.